(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe blood pressure fluctuations in patients with end-stage renal disease on dialysis at Bach Mai Hospital and related factors. Study subjects and methods: Cross-sectional description was performed on 256 chronic renal failure patients undergoing cyclic hemodialysis. Results: The rate of blood pressure fluctuations during and after hemodialysis was 74.6%, including fluctuations in blood pressure and hypotension. The factors of age, associated hypertension, economic circumstances, health insurance regime, time of hemodialysis, and self-care ability are statistically significant with the patient’s BPH with p < 0,05. Conclusion: Blood pressure fluctuations often occur at any time during and after dialysis, most necessary to closely monitor the patient to promptly detect blood pressure complications for timely treatment.